Differential Effects of Organic Fertilizers on Mustard Pakcoy: Efek Diferensial Pupuk Organik pada Tanaman Sawi Pakcoy - Vania Yusriyah, Talitha Sherly; Miftakhurrohmat, A (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the interplay between different types of liquid organic fertilizer (LOF) and their concentrations on the growth and yield of mustard pakcoy plants, aiming to optimize LOF application for enhanced agricultural outcomes. The research was conducted at a rice field in Seloliman Village, Mojokerto using a factorial randomized design encompassing two types of LOF - goat manure and bamboo root PGPR - applied at concentrations of 10, 20, 30, and 40 ml/l. Data were subjected to ANOVA and BNJ tests. Results indicated that goat manure LOF at 20 ml/l significantly influenced plant height, leaf count, leaf area, and wet weight, but exerted no substantial impact on dry weight and harvest index. In contrast, the use of bamboo root PGPR LOF at 30 ml/l markedly affected root length. The findings underscore the importance of selecting appropriate LOF types and concentrations for specific crop growth parameters, providing valuable insights for agricultural practices and research.Highlights: The application of goat manure LOF at 20 ml/l significantly enhanced various growth parameters of mustard pakcoy plants. The bamboo root PGPR LOF, when used at a concentration of 30 ml/l, notably influenced the root length of the plants. The study underscores the crucial role of LOF type and concentration selection in optimizing specific crop growth metrics. Keywords: Liquid Organic Fertilizer, Goat Manure LOF, Bamboo Root PGPR LOF, Mustard Pakcoy Growth, Fertilizer Concentration